2016
DOI: 10.3847/2041-8205/827/2/l31
|View full text |Cite
|
Sign up to set email alerts
|

Mergers of Charged Black Holes: Gravitational-Wave Events, Short Gamma-Ray Bursts, and Fast Radio Bursts

Abstract: The discoveries of GW 150914, GW 151226, and LVT 151012 suggest that double black hole (BH-BH) mergers are common in the universe. If at least one of the two merging black holes carries certain amount of charge, possibly retained by a rotating magnetosphere, the inspiral of a BH-BH system would drive a global magnetic dipole normal to the orbital plane. The rapidly evolving magnetic moment during the merging process would drive a Poynting flux with an increasing wind power. The magnetospheric activities during… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
162
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(165 citation statements)
references
References 48 publications
(48 reference statements)
2
162
0
1
Order By: Relevance
“…Recently, Nathanail, Most & Rezzolla (2017) showed that the collapse of a rotating magnetized NS would leave behind a charged spinning (Kerr-Newman) BH. Such a charged BH was also proposed by Zhang (2016) as a product of BH-BH mergers, of which at least one carries a certain amount of charge (see also Liebling & Palenzuela 2016). In our study, if the product of collapsing supra-massive NS is a Kerr-Newman BH, then the BZ power can be provided by the BH itself even if there is no fall-back accretion.…”
Section: Conclusion and Discussionsupporting
confidence: 58%
“…Recently, Nathanail, Most & Rezzolla (2017) showed that the collapse of a rotating magnetized NS would leave behind a charged spinning (Kerr-Newman) BH. Such a charged BH was also proposed by Zhang (2016) as a product of BH-BH mergers, of which at least one carries a certain amount of charge (see also Liebling & Palenzuela 2016). In our study, if the product of collapsing supra-massive NS is a Kerr-Newman BH, then the BZ power can be provided by the BH itself even if there is no fall-back accretion.…”
Section: Conclusion and Discussionsupporting
confidence: 58%
“…Fermi found a sub-threshold gamma-ray source in a region of the sky that overlapped the ∼600-square-degree LIGO uncertainty region for GW150914 [3]. Though it may be impossible to confirm that the events are indeed physically related, the EM observation has inspired a number of papers exploring potential scenarios linking EM counterparts to stellar-mass black hole mergers [4][5][6][7][8][9][10]-mergers that theorists had expected to be electromagnetically dark.…”
Section: Introductionmentioning
confidence: 99%
“…Whether a BH-BH merger system could have an EM counterpart still needs further observations (see a tentative candidate GW150914-GBM claimed by the Fermi/GBM team (Connaughton et al 2016) and counter opinions (Xiong 2016;Greiner et al 2016); and some theoretical models (Zhang 2016;Loeb 2016;Perna et al 2016) and counter opinions ). GW signals from NS-NS and NS-BH mergers, on the other hand, are highly expected to be associated with EM signals (e.g.…”
mentioning
confidence: 99%